Unpublished research by Kateryna Lazarevska on history of Ukrainian costume of 17th-19th centuries - Koval Tetiana (Рукописна та книжкова спадщина України)

(untitled)
Purpose. To study Kateryna Lazarevska’s unpublished work on the history of Ukrainian costume of the 17th and 19th centuries, which is kept in the collection of the Institute of Manuscript of the V.I. Vernadskyi National Library of Ukraine. Methodology of the research comprises the whole of principles of historical method, objectivity; the main research methods are chronological, retrospective, thematic, source studies, archival studies. The scientific novelty of the work lies in the fact that for the first time the research of K. Lazarevska on the history of Ukrainian costume of the 17th and 19th centuries was processed and introduced into scientific circulation. An array of historical sources and illustrated materials that significantly complement the information on the use of Ukrainian traditional clothing of the 17th and 19th centuries is identified. Conclusions. The collections of the Institute of Manuscript of the V.I. Vernadskyi National Library of Ukraine contain a work by K. Lazarevska, unknown to the general public, which significantly expands the understanding of Ukrainian traditional costume of the 17th and 19th centuries. Summarising information from various historical sources, she provides a clear social differentiation of the traditional costumes of the population of Ukrainian lands, in particular, of the Left Bank Ukraine, with a more detailed description of the clothes, which were marked by a variety of forms and richness of artistic decoration. The work of K. Lazarevska and the documents used in the study preserve important information about the life, customs, and clothing of the Ukrainian people of that period.